Plasmid Vectors for Testing In Vivo Promoter Activities in Corynebacterium glutamicum and Rhodococcus erythropolis - Knoppová, Monika; Phensaijai, Mongkol; Veselý, Martin; Zemanová, Martina; Nešvera, Jan; Pátek, Miroslav (Current microbiology, 2007)
Novel shuttle promoter-probe vectors replicating in Escherichia coli, Corynebacterium glutamicum, and Rhodococcus erythropolis were constructed on the basis of the C. glutamicum plasmid pCG1. The vectors carry reporter genes coding for fluorescent proteins, which allow the measurement of promoter activities in vivo. The promoter-probe vector pPRE11 contains the rsgfp reporter gene, coding for a variant of green fluorescent protein (GFP) with a red-shifted excitation maximum. To ensure efficient expression of the gfp gene in R. erythropolis from the tested promoters, the promoterless gene gfpuv, with 5' end fusion with the initial six codons of the aph gene and upstream insertion of the aph Shine-Dalgarno sequence, was used as a reporter gene in the promoter-probe vector pEPR1. Insertion of the rfp reference gene, coding for a variant of the red fluorescent protein DsRed.T4 and cloned under the strong constitutive C. glutamicum promoter P-45, into the vector pEPR1 resulted in a new-generation promoter-probe vector (pRAG5). All vectors were tested using a set of mutant P-dapA promoters displaying various transcriptional activities. The vector pRAG5 is suitable for normalized measurements of promoter activities during the growth of bacterial batch cultures because estimation of the GFP-to-red fluorescent protein fluorescence ratio in strains carrying the plasmid pRAG5 with the tested promoters upstream of gfpuv avoids the influence of plasmid copy number variations on the promoter activity assay.